Bangladesh economy in the 21st century : selected papers from the 2008 and 2009 conferences on Bangladesh at Harvard University - Quddus, Munir; Khan, Farida C. (Farida Chowdhury); Harvard University; Bangladesh Development Initiative (Dhaka : Bangladesh Development Initiative : University Press Limited, 2011)
Contributed sections on economic development, foreign investments, and performance of services industries of Bangladesh.
Includes statistical tables.
Includes bibliographical references and index.
00025683
Keywords: Economic development -- Bangladesh -- Congresses; Investments, Foreign -- Bangladesh -- Congresses; Service industries -- Bangladesh -- Congresses